Factors associated with participation status in cardiac rehabilitation: A single centre experience - Samsudin, Luqman; Hamdi, Hanie Farhana; Mohamad Aziz, Muhammad Hafizuddin; Suhaimi, Anwar; Pasi, Hafizah (2017)
Background Despite its proven benefits, participation in cardiac rehabilitation (CR) still remains low globally. The predictors of participation in this programme have been widely studied abroad however, in Malaysia, the data in this field is scarce as the programme is relatively new. Objective The aim of this study is to investigate the relationship between status of participation with sociodemographic, logistic and clinical health status. Methods A cross-sectional study was done in University Malaya Medical Centre, Malaysia. A total of 45 respondents of outpatient Phase II CR were selected through convenient sampling. The respondents completed sociodemographic and logistic survey through face-to-face and telephone-based interview. The clinical health status data were obtained from medical records. Data received were analyse using SPSS version 24.0. The percentage of each variable was calculated and the differences were tested using t-test and chi-square test where applicable. Multiple logistic regression was performed. Statistical significance was set at p <0.05. Results 51% of respondents were participants while 49% were non-participants. Univariate analysis revealed significant difference of more non-participants had medical comorbidities while more participants perceived already exercise (p<0.05). However, multiple logistic regression of the status of participation with sociodemographic, logistic and clinical health status shows no statistical significant predictors in the final model. Discussion Presence of medical comorbidities and exercise status were associated with participation status in CR. Patients education and awareness on CR should be emphasized by health care practitioners. Further studies involving multiple centres with larger cohort of patients should be done to identify predictors for CR participation which can assist the policy maker in structuring the programme to encourage more participation in CR programme.